144 High-sensitivity cardiac troponin and the fourth universal definition of myocardial infarction. (May 2019) - Chapman, Andrew; Adamson, Philip; Shah, Anoop; Anand, Atul; Strachan, Fiona; Lee, Kuan Ken; Ferry, Amy; Sandeman, Dennis; Stables, Catherine; Newby, David; Mills, Nicholas
Abstract : Background: The Universal Definition of Myocardial Infarction recommends the 99th centile diagnostic threshold using a high-sensitivity cardiac troponin (hs-cTn) assay and classification of patients by the etiology of myocardial injury. Whether implementation of this definition improves risk stratification, treatment or outcomes is unknown. Methods: In a stepped-wedge cluster randomized controlled trial, we implemented the recommendations of the Universal Definition of Myocardial Infarction in consecutive patients attending the Emergency Department with suspected acute coronary syndrome across ten hospitals in Scotland. All patients with hs-cTnI concentrations above the sex-specific 99th centile were classified according to the Fourth Universal Definition. The primary outcome was myocardial infarction (type 1 or type 4b) or cardiovascular death at 1 year. In this pre-specified secondary analysis, we compared the primary outcome with the secondary outcome of non-cardiovascular death. Based on prior observations of an excess in non-cardiovascular death in patients with type 2 myocardial infarction and myocardial injury, we applied competing risks methodology in all analyses. Results: We enrolled 48, 282 consecutive patients with suspected acute coronary syndrome. Implementation of the recommendations of the Universal Definition increased the diagnosis of type 1 myocardial infarction by 11% (510/4, 471), type 2 myocardial infarction by 22% (205/916), acute myocardial injury by 36% (443/1, 233) and chronic myocardial injury by 43% (389/898). The proportion of deaths from a cardiovascular and non-cardiovascular cause differed significantly across diagnostic categories (figure 1 ). Compared to those without myocardial injury, the rate of the primary outcome was highest in those with type 1 myocardial infarction (cause-specific hazard ratio [csHR] 5.64, 95% confidence interval [CI] 5.12 to 6.22), whereas non-cardiovascular death was highest in those with acute myocardial injury (csHR 2.65, 95%CI 2.33 to 3.01, figure 2). Despite increases in anti-platelet therapy and coronary revascularization after implementation, the primary outcome was unchanged in patients with type 1 myocardial infarction (csHR 1.00, 95%CI 0.82 to 1.21), or in any other category. Conclusion: Diagnostic classification by the Universal Definition of Myocardial Infarction identifies patients with different risks of future cardiovascular and non-cardiovascular events. Increases in the diagnosis and treatment of myocardial infarction and injury are not associated with improved clinical outcomes. Conflict of Interest: NA